A case history of shield tunnel crossing through group pile foundation of a road bridge with pile underpinning technologies in Shanghai. (January 2015) - Xu, Qianwei; Zhu, Hehua; Ma, Xianfeng; Ma, Zhongzheng; Li, Xiaojun; Tang, Zhuohua; Zhuo, Kui
Highlights: A pile underpinning technology was proposed for shiled tunnel cross through group pile foundation. Theoretical analysis and numerical simulation are carried out on the entire construction process. The Real-time field monitoring results agree well with the numerical calculation ones. Abstract: According to the planning of Shanghai metro line 10, the interval tunnel from Liyang Road station to Quyang Road station has to cross through the group pile foundation of Shajinggang Bridge on Siping Road. Therefore, how to guarantee the normal traffic function and the safety of bridge structure during the tunneling process becomes a challenge to engineers and technicians. To solve this problem, the pile underpinning technology was recommended for this project. This specific scheme mainly comprises following steps, i.e. ground improvement behind abutment, foundation pit excavation under bridge deck, underpinning pile with raft and cutting pile with shield machine directly, etc. In order to verify the feasibility of this scheme, a series of theoretical analysis and numerical simulation were carried out on the entire construction process to explore the load transfer mechanism of bridge structure. The calculation results show that both the bridge static loads and traffic live loads can be successfully transferred from pile foundation to raft after pile underpinning, and the removal of obstructed piles during tunneling has very limited influence on bridge structure. Furthermore, real-time field monitoring activities, including settlement of bridge deck surface, deformation of surrounding buildings and pipelines, etc. were also conducted to ensure smooth construction. The monitored results agree well with the numerical calculation ones, which prove again that the proposed scheme is reasonable and the calculation results are reliable.